Kontribusi Pendidikan Islam Andalusia dalam Perkembangan Intelektual Barat - Rendi Saputra; Sulis Maryati; Tri Anugrah (CV. ITTC INDONESIA, 2026)
Islamic civilization in Al-Andalus was one of the most influential centers of education and scientific development during the Middle Ages. This article aims to examine the contribution of Islamic education in Al-Andalus to the advancement of knowledge in Europe through a qualitative literature review. The study employs a library research method by analyzing relevant books, scholarly journals, and historical sources related to the educational system and intellectual achievements of Al-Andalus. The findings indicate that educational institutions such as mosques, kuttab, libraries, madrasas, and universities played a significant role in promoting learning and scientific inquiry.These institutions integrated religious and secular sciences, including philosophy, medicine, mathematics, astronomy, and natural sciences, creating an environment that encouraged critical thinking and innovation. In addition, the translation movement, particularly in Toledo, facilitated the transmission of Arabic scientific and philosophical works into Latin, enabling European scholars to access and develop Islamic knowledge. Prominent Muslim scholars such as Ibn Rushd, AlZahrawi, Abbas Ibn Firnas, and Ibn Hazm made substantial contributions to philosophy, medicine, engineering, and education. Their works became important references in European universities and significantly influenced the intellectual revival that led to the Renaissance. The study concludes that Islamic education in Al-Andalus was not limited to religious instruction but functioned as a comprehensive system that advanced science, encouraged cultural exchange, and strengthened intellectual development.The educational legacy of Al-Andalus demonstrates the importance of integrating faith, knowledge, and ethical values in fostering innovation and academic excellence. These contributions remain relevant for contemporary education in promoting interdisciplinary learning, scientific research, and international collaboration.